The genome sequence of the moss carder bee, Bombus muscorum (Linnaeus, 1758) [version 1; peer review: 2 approved] - Ian Barnes; Gavin R. Broad (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Bombus muscorum (the moss carder bee; Arthropoda; Insecta; Hymenoptera; Apidae). The genome sequence spans 317.70 megabases. Most of the assembly is scaffolded into 17 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 21.15 kilobases in length. Gene annotation of this assembly on Ensembl identified 11,668 protein-coding genes.